Respuesta :

Answer:

y = (6/5)x + 29/5

Step-by-step explanation:

To avoid confusion please enclose the fractional exponent inside parentheses:  y= -5/6x +3 =>  y= (-5/6)x +3

The new line is to be perpendicular to the given line (above).  The slope of this new line must be the negative reciprocal of (-5/6), which is (6/5).

Usig the slope-intercept formula, we get y = mx + b, or

1 = (6/5)(-4) + b

The LCD here is 5.  Multiplying all 3 terms by 5, we get:

5 = 6(-4) + 5b, or

5 = -24 + 5b, or

5b = 29

Then b = 29/5, and the desired equation is:

y = (6/5)x + 29/5